ANALISIS VARIABEL MAKRO DAN FAKTOR LUAR NEGERI PADA IHSG PERIODE 2004-2007 - Bonnie Mindosa (Jurnal Ekonomi Perusahaan, 2017)
The objective of this study is to examine the impact of macro economy variables, such as: GDP, INFLATION, EXCHANGE RATE, SBI RATE and eksternal factors, such as: HANG SENG INDICES and INTERNATIONAL OIL PRICE toward capital market in Indonesia. The data that used in this study is quarterly since 2004 to 2007. The examination using multiple regression ordinary least square and the classic assumption test is conducted previously. The results revealed that all variables satisfy the ordinary least square basic assumption. The model could describe the variant of independent variable 98% and all variables have strong correlation. The first hypothesis test explained that all variables affect simultaneously and the second hypothesis test explained that only GDP, SBI RATE and INTERNATIONAL OIL PRICE affect IHSG with 5% significant level meanwhile GDP become the dominant variable.Keywords: Macro variables, Eksternal factors, Classic assumption and Multiple regression.